Anne of a different island - Kantra, Virginia (Berkley, 2026)
"A woman must learn to take responsibility for her own dreams in this heartfelt novel inspired by Anne of Green Gables by New York Times bestselling author Virginia Kantra. Anne Gallagher believes in love-the kind of love that exists in fairy tales and romance novels and-most of all-in her favorite book of all time, Anne of Green Gables. Growing up on isolated Mackinac Island, Michigan, she imagined herself as Anne Shirley. There's the name, right? And her hair is red-well, reddish. And while Mackinac is no Prince Edward Island, it does have a tiny island school and horse-drawn carriages on a main street lined with Victorian houses. She dreams of becoming a teacher and a writer, just like her fictional role model. Everything is falling into place for Anne, who is getting ready to graduate from Northwestern University and has already lined up a job at a pricey private school north of Chicago. She's also dating her very own Gilbert Blythe-a selfless medical resident named Chris, whose rich family used to vacation on Mackinac in the summers. But then Anne's beloved father dies from a heart attack while working on a roof, and a dispute with her new principal leads to a leave of absence. Now she must return home to Mackinac, which means confronting all the strained relationships she left behind. With nothing but time back on the island known for its beauty and charm, Anne has a chance to reconsider her decisions and decide for herself what she wants out of life."-- Provided by publisher.